Dampak E-Service Quality, Kepercayaan dan Kepuasaan Terhadap Niat Pembelian Ulang - Joko Rizkie Widokarti; Arthur Sitaniapessy; Harry Anthony Pierre Sitaniapessy (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2023)
Nowadays, consumer purchasing behavior is increasingly shifting to online purchases which promise a lot of convenience. This study aims to examine the effect of E- Service Quality, Trust, and Customer Satisfaction on repurchase intentions in the context of online purchases on e-commerce sites in Indonesia. The sample size in this study was 177 respondents. Hypothesis testing was carried out using multiple regression analysis. The results showed that e-service quality, customer trust as well as customer satisfaction had a positive impact on repurchase intention.